Computational micromechanics of fiber kinking in unidirectional FRP under different environmental conditions. (26th May 2017) - Naya, F.; Herráez, M.; Lopes, C.S.; González, C.; Van der Veen, S.; Pons, F.
Abstract: The determination of ply properties of Fiber Reinforced Polymers (FRP) for particular operational environmental conditions in aeronautical applications is mandatory in order to fulfill current industry stringent certification requirements. However, the traditional experimental approach requires massive investments of resources and time. From the behaviour obtained experimentally, constitutive equations including failure criteria are then devised to be used in the design of FRP structures. The ply longitudinal behaviour under compression is generally the most difficult to measure and characterize. In this work, an alternative coupled experimental-computational micromechanics approach is proposed to determine the longitudinal compression properties of unidirectional FRP plies under different environmental conditions. This methodology includes experimental characterization of matrix and fiber/matrix interface, combined with numerical simulations of realistic microstructures. The interface decohesion is simulated using cohesive-frictional interactions. A pressure dependent, elasto-plastic model that includes tensile damage is employed to capture the matrix nonlinear behaviour. The numerical predictions match the experimentally-obtained ply properties available in the literature in a remarkable way and suggest that virtual ply property characterization is a mature and reliable approach to conduct screening of materials.